Dose dependent and divergent effects of superoxide anion on cell death, proliferation, and migration of activated human hepatic stellate cells. Issue 1 (24th July 2005) - Novo, E; Marra, F; Zamara, E; Valfrè di Bonzo, L; Caligiuri, A; Cannito, S; Antonaci, C; Colombatto, S; Pinzani, M; Parola, M
Abstract : Background and aim: Activated myofibroblast-like cells, originating from hepatic stellate cells (HSC/MFs) or other cellular sources, play a key profibrogenic role in chronic liver diseases (CLDs) that, as suggested by studies in animal models or rat HSC/MFs, may be modulated by reactive oxygen intermediates (ROI). In this study, human HSC/MFs, exposed to different levels of superoxide anion (O2 − ) and, for comparison, hydrogen peroxide (H2 O2 ), were analysed in terms of cytotoxicity, proliferative response, and migration. Methods: Cultured human HSC/MFs were exposed to controlled O2 − generation by hypoxanthine/xanthine oxidase systems or to a range of H2 O2 concentrations. Induction of cell death, proliferation, and migration were investigated using morphology, molecular biology, and biochemical techniques. Results: Human HSC/MFs were shown to be extremely resistant to induction of cell death by O2 − and only high rates of O2 − generation induced either necrotic or apoptotic cell death. Non-cytotoxic low levels of O2 −, able to upregulate procollagen type I expression (but not tissue inhibitor of metalloproteinase 1 and 2), stimulated migration of human HSC/MFs in a Ras/extracellular regulated kinase (ERK) dependent, antioxidant sensitive way, without affecting basal or platelet derived growth factor (PDGF) stimulated cell proliferation. Non-cytotoxic levels of H2 O2 did not affect Ras/ERK or proliferative response. A high rate of O2 − generation or elevated levels of H2 O2 induced cytoskeletal alterations, block in motility, and inhibition of PDGF dependent DNA synthesis. Conclusions: Low non-cytotoxic levels of extracellularly generated O2 − may stimulate selected profibrogenic responses in human HSC/MFs without affecting proliferation.